Azadirachta Indica (Semambu) in Traditional Malay Medical manuscripts and assessment of bioactive compounds - Razanah Ramya; Rashidi Othman; Farah Ayuni Mohd Hatta; Wan Syibrah Hanisah Wan Sulaiman; Nur Hanie Mohd Latiff (Penerbit Universiti Kebangsaan Malaysia, 2024)
Azadirachta indica (neem) is an Asia native plant from Meliaceae family, which has been recognized for its pharmaceutical potential for ages and contain numerous bioactive phytochemicals with therapeutic potential. This research aims to examine the ethnomedicinal plants that have been recorded in transliterated manuscripts and to discover the bioactive compounds. For methodology, secondary data were obtained from five selected Malay medical books. The experimental design involved two extraction methods, namely water extraction and sequential alkaline extraction. The data was qualitatively and quantitatively analyzed by Total Phenolic Content (TPC), and High-Performance Liquid Chromatography (HPLC). The findings from the Malay medical manuscript indicate that most diseases were physical illnesses. The total phenolic content of A. indica was 779.89 ± 12.32 μg GAE/g DW, and the phenolic acids detected by HPLC in both extractions were Vanillic acid, trans-p-coumaric acid, and ferulic acid. In conclusion, this study demonstrates that A. indica has a huge potential for further exploration in pharmaceuticals.